2024
DOI: 10.3390/foods13050733
|View full text |Cite
|
Sign up to set email alerts
|

Microalgae Proteins as Sustainable Ingredients in Novel Foods: Recent Developments and Challenges

Ornella Kongi Mosibo,
Giovanna Ferrentino,
Chibuike C. Udenigwe

Abstract: Microalgae are receiving increased attention in the food sector as a sustainable ingredient due to their high protein content and nutritional value. They contain up to 70% proteins with the presence of all 20 essential amino acids, thus fulfilling human dietary requirements. Microalgae are considered sustainable and environmentally friendly compared to traditional protein sources as they require less land and a reduced amount of water for cultivation. Although microalgae’s potential in nutritional quality and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 149 publications
0
1
0
Order By: Relevance
“…For example, Irish moss ( Chondrus crispus ) ( Figure 4 ), a red alga commonly found in the Atlantic Ocean, contains a moderate amount of protein, along with carrageenan, a polysaccharide used as a thickening agent in food products. Irish moss is also rich in vitamins, minerals, and antioxidants and has been traditionally used to support respiratory health and digestive function [ 90 , 91 ]. Sea lettuce ( Ulva spp.…”
Section: Algae Proteins and Amino Acidsmentioning
confidence: 99%
“…For example, Irish moss ( Chondrus crispus ) ( Figure 4 ), a red alga commonly found in the Atlantic Ocean, contains a moderate amount of protein, along with carrageenan, a polysaccharide used as a thickening agent in food products. Irish moss is also rich in vitamins, minerals, and antioxidants and has been traditionally used to support respiratory health and digestive function [ 90 , 91 ]. Sea lettuce ( Ulva spp.…”
Section: Algae Proteins and Amino Acidsmentioning
confidence: 99%
“…In addition, protein is crucial in sustaining normal physiological functions, regulating bodily processes, and providing energy. Inadequate protein consumption can result in malnutrition [ 1 , 13 , 18 ].…”
Section: Microalgal Ingredients For Food Applicationmentioning
confidence: 99%
“…However, this unsustainable approach leads to environmental degradation and resource depletion. Researchers are exploring alternative food sources to address the future demand for ingredients, particularly protein [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to Doan et al [5], in human nutrition, Spirulina finds favor not only for its remarkable protein content, which can reach up to 70% of its dry matter, but also for its composition of essential amino acids (AAs) and its high digestibility, positioning it as a promising alternative protein source. Moreover, proteins derived from microalgae exhibit favorable technological properties, serving as effective foaming, gelling, and emulsifying agents [6][7][8]. Numerous studies have demonstrated the competitive edge of microalgae proteins against commercially used emulsifiers like sodium caseinate, whey protein, and soy protein [9,10].…”
Section: Introductionmentioning
confidence: 99%